Western Balkans - Public Investment Management Study : Main Report - World Bank (World Bank, 2012)
This report summarizes the findings of a review of public investment management (PIM) practices in the Western Balkans carried out with an eye to improving practices over the medium term, sharing experiences on a regional basis, providing some initial specific recommendations and identifying areas for more intensive further analysis. Following this introduction, the second section of the main report examines capital expenditure trends in the study countries. The third section provides an overview of the findings across the six countries. The fourth section provides potential drill-down topics for the further analysis. The fifth and final section briefly outlines the methodology used in the individual country studies. The study has revealed frequent weaknesses in the institutional arrangements for public investment management, although in most cases things are moving in the right direction. Box one set out some stylized guidelines on good practice for institutional arrangements for public investment management, based on what is commonly found in OECD countries. The box describes systems involving a single, integrated budgeting process for capital and recurrent expenditure, within which capital expenditure is clearly distinguished from current expenditure because of its particular characteristics.